When does a communication to the public under EU copyright law need to be to a "new public"? - Rosati, Eleonora (European law review, 2020)
Abstract.
Keywords: tekijänoikeus; tekijänoikeus : EU-oikeus; oikeustapaukset : Euroopan unionin tuomioistuin; yleisölle välittäminen tekijänoikeudessa